2003
DOI: 10.1038/sj.leu.2402996
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for patients with chronic myeloid leukaemia in chronic phase treated with imatinib mesylate after failure of interferon alfa

Abstract: We assessed clinical results in 145 patients with chronic myeloid leukaemia in chronic phase who satisfied criteria for interferon-a failure and were thus eligible for treatment with imatinib at the Hammersmith Hospital. We used univariate and multivariate analyses to develop a risk score based on features defined after treatment for 3 months. We identified a low neutrophil count and poor cytogenetic response (o35% Phnegative marrow metaphases) at 3 months as principal independent predictive factors and incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 15 publications
2
32
1
1
Order By: Relevance
“…While the negative impact of early anemia has been already demonstrated in different studies [16,17], in our cohort of patients persistent/late chronic anemia did not seem to affect EFS and OS; this finding, however, needs to be confirmed in independent and larger series of patients. Finally, the retrospective nature of our study did not allow us to make any consideration on QoL in patients with chronic anemia.…”
Section: Discussionsupporting
confidence: 60%
“…While the negative impact of early anemia has been already demonstrated in different studies [16,17], in our cohort of patients persistent/late chronic anemia did not seem to affect EFS and OS; this finding, however, needs to be confirmed in independent and larger series of patients. Finally, the retrospective nature of our study did not allow us to make any consideration on QoL in patients with chronic anemia.…”
Section: Discussionsupporting
confidence: 60%
“…9 We reported previously the predictive value of the Sokal score in patients in late chronic phase who receive imatinib as a second-line therapy, 26 and we highlighted the adverse prognostic implications of cytopenias in imatinib-treated patients. 2,26 We also found that the time elapsed from first identification of imatinib treatment failure to beginning therapy with a second-generation TKI was a significant independent predictor of lack of complete cytogenetic response (Table 1). This could support the recommendation that patients proven resistant to imatinib 400 mg/day should be started on a second-generation TKI as soon as feasible.…”
Section: A B C Dmentioning
confidence: 99%
“…10 In these cases, the poor prognosis associated with hematologic toxicity may in part explained by the lack of an expandable population of Philadelphia chromosomenegative cells. 12 We report here the largest series of CML patients in CP treated with a third-line TKI after failing both imatinib and another TKI. Our rather disappointing results stress the need to select more carefully the patients who may benefit from a third line TKI, as for many patients allogeneic stem cell transplantation or an alternative experimental therapy may be a more appropriate.…”
Section: Influence Of Response On Outcomementioning
confidence: 99%
“…Patients who had had nonhematologic side effects as the primary reason for change of therapy fared well, whereas patients with a history of hematologic toxicity to one of the prior TKIs fared worse. We have previously reported the association between hematologic toxicity and lack of cytogenetic response in CP patients treated with imatinib as first-line therapy, 11 in patients treated with imatinib after interferon-␣ failure, 12 and in patients treated with nilotinib or dasatinib after imatinib failure. 10 In these cases, the poor prognosis associated with hematologic toxicity may in part explained by the lack of an expandable population of Philadelphia chromosomenegative cells.…”
Section: Influence Of Response On Outcomementioning
confidence: 99%